Using an ultra-thin non-doped orange emission layer to realize high efficiency white organic light-emitting diodes with low efficiency roll-off - Zhu, Liping (2014)
By adopting an ultra-thin non-doped orange emission layer sandwiched between two blue emission layers, high efficiency white organic light-emitting diodes (WOLEDs) with reduced efficiency roll-off were fabricated. The optimized devices show a balanced white emission with Internationale de L'Eclairage of (0.41, 0.44) at the luminance of 1000 cd/m2, and the maximum power efficiency, current efficiency (CE), and external quantum efficiency reach 63.2 lm/W, 59.3 cd/A, and 23.1%, which slightly shift to 53.4 lm/W, 57.1 cd/A, and 22.2% at 1000 cd/m2, respectively, showing low efficiency roll-off. Detailed investigations on the recombination zone and the transient electroluminescence (EL) clearly reveal the EL processes of the ultra-thin non-doped orange emission layer in WOLEDs.